Thrombosis of the Abdominal Aorta in a Extremely Low Birth Weight Infant: Treatment with Tissue-Type Plasminogen Activator - Bertini, Giovanna; Elia, Serena; Vangi, Venturella (International Journal of Pediatrics and Child Health, 2020)
Aortic thrombosis during neonatal period is a rare event especially when it is not related to umbilical arterial catheters. A case of a premature infant with a gestational age of 25 weeks who suddenly developed, at the age of 44 days, poor arterial saturation (SaO2 60%) and legs pale and painful, is reported. In this patient, arterial and venous eco-color Doppler showed a complete aortic thrombosis distal to the renal arteries of unknown etiology. Thrombolytic therapy with tissue-type plasminogen activator (t-PA) was immediately started with a bolus dose of 0.5 mg/kg/h followed by a continuous infusion of 0.2 mg/kg/h. Fresh frozen plasma was also infused in order to increase the concentration of plasminogen. We tried with success to avoid bleeding complications maintaining fibrinogen concentration over 500 mg/L and platelets over 100,000x109/L. Heparinisation with enoxaparin was started after 5 days of t-PA treatment and continued for 85 days. The premature infant recovered but physiotherapy and splints were needed for talipes equinovarus resulted as a consequence of distal thrombosis. Conclusion: The strategy for treating an acute arterial thrombosis in a neonate may include thrombolytic therapy with t-PA, taking into account that the rate of plasmin generation in newborns and overall activity is decreased compared to adults. The impaired response of newborns may be enhanced not by increasing the dose of t-PA but increasing plasminogen through fresh frozen plasma infusion.